2013
DOI: 10.1021/bi4010232
|View full text |Cite
|
Sign up to set email alerts
|

Second-Sphere Interactions between the C93–Y157 Cross-Link and the Substrate-Bound Fe Site Influence the O2 Coupling Efficiency in Mouse Cysteine Dioxygenase

Abstract: Cysteine dioxygenase (CDO) is a non-heme iron enzyme that catalyzes the O₂-dependent oxidation of l-cysteine (l-Cys) to produce cysteinesulfinic acid (CSA). Adjacent to the Fe site of CDO is a covalently cross-linked cysteine-tyrosine pair (C93-Y157). While several theories have been proposed for the function of the C93-Y157 pair, the role of this post-translational modification remains unclear. In this work, the steady-state kinetics and O₂/CSA coupling efficiency were measured for wild-type CDO and selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
156
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(187 citation statements)
references
References 74 publications
13
156
2
Order By: Relevance
“…Either way, the C164S variant is unable to deprotonate in this pH range and/or form this disulfide and therefore is able to be fully crosslinked, in contrast to WT. In contrast to our results with WT, Pierce and coworkers have been able to form fully crosslinked WT mouse CDO, [11] something we have been unable to do using our protein and methods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Either way, the C164S variant is unable to deprotonate in this pH range and/or form this disulfide and therefore is able to be fully crosslinked, in contrast to WT. In contrast to our results with WT, Pierce and coworkers have been able to form fully crosslinked WT mouse CDO, [11] something we have been unable to do using our protein and methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, we and others have shown that mammalian CDO activity is dependent upon the amount of crosslink. [11,12] Indeed, the kinetic parameters of the two isoforms were shown to be quite different. [13] A second posttranslational modification forms in mammalian CDO; a disulfide between cysteine 164 and exogenous cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…This species exhibits a g -spread similar to, though slightly smaller than, that of the (N 3 – /Cys)-Fe(III)CDO adduct (Δ g = 0.442 for the cyanide adduct, as compared to Δ g = 0.547 for the azide-bound species). 18 The small differences in g -spread likely reflect a more delocalized “SOMO” and/or smaller splitting of the “t 2g set” of Fe 3d-based MOs (due to π-backbonding) in the (CN – /Cys)-Fe(III)CDO species.…”
Section: Resultsmentioning
confidence: 99%
“…19 Although eukaryotic forms of CDO are catalytically competent if the cross-link is not formed, enzymatic activity increases drastically (>20-fold) when the cross-link is present. 18 Notably, prokaryotic versions of CDO lack this cross-link, yet they maintain a similar level of activity as eukaryotic, cross-linked CDO. 20 …”
mentioning
confidence: 99%
See 1 more Smart Citation